Pengaruh Pendidikan Anak Usia Dini terhadap Prestasi Belajar Siswa Kelas I Sekolah Dasar di Kabupaten dan Kota Tangerang - Aceng Lukmanul Hakim (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2011)
Early Childhood Education (ECE) is an institute carrying out a formal education for children age 0-6 before entering elementary school. This foundation aims to continue the education as well as to execute parents’s commendation that has been putting down in the family, where as the elementary school (ES) is the institution of education that prepared children age 6-13 for entering next education. The students of elementary school, who were from early childhood education have shown up achievement compared to those who were not. This achievement is not only in intellectual aspec, but in psychomotoric aspec, value and attitude with a significant performant. That achievement is not only at Tangerang City, but at Tangerang Major. On the other hand hadmaster and the teacher’s first class in elementary school at Tangerang City inclined have a way of view of education more higher than at Tangerang Major.ABSTRAK Pendidikan anak usia dini adalah lembaga yang menyelenggarakan pendidikan formal bagi anakanak yang berumur 0-6 tahun sebelum memasuki sekolah dasar. Lembaga ini membantu melanjutkan pendidikan yang dasar-dasarnya telah diletakkan oleh orang tua dalam keluarga, sedangkan sekolah dasar adalah lembaga pendidikan yang dipersiapkan bagi anak-anak umur 6-13 tahun guna memasuki jenjang pendidikan selanjutnya. Siswa sekolah dasar yang mengikuti pendidikan anak usia dini lebih berprestasi dari pada siswa yang tidak mengikutinya. Prestasi ini tidak hanya pada aspek intelektual, namun juga aspek psikomotorik, nilai dan sikap dengan perbedaan yang signifikan. Prestasi ini pun tidak hanya di Kota Tangerang, melainkan juga di Kabupaten Tangerang. Di pihak lain kepala sekolah dasar dan guru kelas I di Kota Tangerang cenderung memiliki cara pandang terhadap pendidikan lebih tinggi dari pada di Kabupaten Tangerang.